Optically accessible, 3D-printed flow chamber with integrated sensors for the monitoring of oral multispecies biofilm growth in vitro - Debener, Nicolas; Heine, Nils; Legutko, Beate; Denkena, Berend; Prasanthan, Vannila; Frings, Katharina; Torres-Mapa, Maria Leilani; Heisterkamp, Alexander; Stiesch, Meike; Doll-Nikutta, Katharina; Bahnemann, Janina (Frontiers in Bioengineering and Biotechnology, 2024)
The formation of pathogenic multispecies biofilms in the human oral cavity can lead to implantassociated infections, which may ultimately result in implant failure. These infections are neither easily detected nor readily treated. Due to high complexity of oral biofilms, detailed mechanisms of the bacterial dysbiotic shift are not yet even fully understood. In order to study oral biofilms in more detail and develop prevention strategies to fight implant-associated infections, in vitro biofilm models are sorely needed. In this study, we adapted an in vitro biofilm flow chamber model to include miniaturized transparent 3D-printed flow chambers with integrated optical pH sensorsthereby enabling the microscopic evaluation of biofilm growth as well as the monitoring the acidification in close proximity. Two different 3D printing materials were initially characterized with respect to their biocompatibility and surface topography. The functionality of the optically accessible miniaturized flow chambers was then tested using five-species biofilms (featuring the species Streptococcus oralis, Veillonella dispar, Actinomyces naeslundii, Fusobacterium nucleatum, and Porphyromonas gingivalis) and compared to biofilm growth on titanium specimens in the established flow chamber model. As confirmed by live/dead staining and fluorescence in situ hybridization via confocal laser scanning microscopy, the flow chamber setup proved to be suitable for growing reproducible oral biofilms under flow conditions while continuously monitoring biofilm pH. Therefore, the system is suitable for future research use with respect to biofilm dysbiosis and also has great potential for further parallelization and adaptation to achieve higher throughput as well as include additional optical sensors or sample materials.